Empowerment of Micro, Small, and Medium Enterprises in Villages Based on Technology Through Community Service Programs - Sopingi, Imam; Zeffa , Ahmad; Yumna, Hanin (Jurnal Al Maesarah, 2025)
The community service program titled "Technology-Based Village MSME Empowerment" aims to enhance the competitiveness of rural MSMEs through digital technology adoption and financial management training. The program employed various methods, including lectures, hands-on training, group discussions, Q&A sessions, simulations, and post-training evaluations. A total of 102 MSME entrepreneurs from diverse sectors—culinary, handicrafts, fashion, and services—participated in the training held in Jombang. The training covered topics such as digital technology introduction, digital marketing strategies, the utilization of digital applications for business operations, and business collaboration techniques. Evaluation results indicated that 78% of participants found the training highly beneficial for business development in digital marketing, 70% successfully enhanced their digital marketing effectiveness, and 65% improved their financial management capabilities. The findings demonstrate that an integrated, technology-driven approach can help MSMEs adapt to the digital era, boost revenue, and strengthen business sustainability. The program concludes by emphasizing the importance of continuous training through multi-stakeholder collaboration, mentorship, and digital infrastructure development. This initiative presents an effective MSME empowerment model that can be adapted and implemented on a broader scale, considering local needs and conditions.